2022
DOI: 10.1094/pdis-01-22-0038-re
|View full text |Cite
|
Sign up to set email alerts
|

Long-Distance Transport of Puccinia striiformis f. sp. tritici by Upper Airflow on the Yunnan–Guizhou Plateau Disrupts the Balance of Agricultural Ecology in Central China

Abstract: Long-distance dispersal of plant pathogens in the air can establish diseases in other areas and lead to an increased risk of large-scale epidemics. Wheat stripe rust, caused by Puccinia striiformis f. sp. tritici (Pst), is one of the most destructive diseases of wheat in China. Hubei is an important overwintering region for Pst in China, and this overwintering region is a determinant of stripe rust severity in eastern China. In 2017, stripe rust disease caused a pandemic in the Hubei region and resulted in gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…According to the analysis of wind and airflow trajectory from November 2018 to February 2019, a south‐westerly wind prevailed in Yunnan during this period, and the Pst urediniospores can be taken along with the south‐westerly wind from Yunnan to southern Hubei, and then continue to spread to Zhejiang and other MLRYR. Some previous research results supported this deduction (Huang et al, 2022; Ju et al, 2022; Li et al, 2021). The sampling time of wheat stripe rust showed a gradually postponed trend from Kunming, Jingzhou to Hangzhou, implying a time delay of wheat stripe rust occurrence in the field from western to eastern regions.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…According to the analysis of wind and airflow trajectory from November 2018 to February 2019, a south‐westerly wind prevailed in Yunnan during this period, and the Pst urediniospores can be taken along with the south‐westerly wind from Yunnan to southern Hubei, and then continue to spread to Zhejiang and other MLRYR. Some previous research results supported this deduction (Huang et al, 2022; Ju et al, 2022; Li et al, 2021). The sampling time of wheat stripe rust showed a gradually postponed trend from Kunming, Jingzhou to Hangzhou, implying a time delay of wheat stripe rust occurrence in the field from western to eastern regions.…”
Section: Discussionmentioning
confidence: 57%
“…Yunnan was previously considered to be an independent epidemic area of wheat stripe rust with no exchange with other geographical groups (Zeng & Luo, 2008), but recent evidence has proved that there is an exchange of Pst inoculum sources between Yunnan and Hubei and the MLRYR. The inoculum source of Pst in southern Hubei is mainly from Yunnan, and the Yunnan provided major inoculum sources to Jiangsu and Zhejiang regions (Huang et al, 2022; Ju et al, 2022). In the present study, we found that the inoculum source of Pst in Zhejiang is also mainly from Yunnan, and that the south of Hubei serves as a transfer station (or stopover) for the inoculum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its specific inoculum centers and their related dispersal routes have not been clear. Recently, much intensive research has been performed to investigate Pst dispersal patterns in China, although it has focused on studying relationships among Pst populations in a few regions using a handful of molecular markers ( Liang et al., 2013 , 2016 , 2021 ; Wan et al., 2015 ; Wang et al., 2020 , 2022 ; Huang et al., 2021 , 2022 ; Zhan et al., 2022 ). Analyses based on a limited number of markers and sampling sites may not provide sufficient resolution to dissect the genetic diversity and structure of Pst populations ( Hubbard et al., 2015 ; Bueno-Sancho et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, this epidemiological region is almost isolated from other regions. However, recent studies revealed that the Yunnan epidemiological region and other southwestern epidemiological regions are also involved in wheat stripe rust epidemics in China (Awais et al 2022;Huang et al 2022;Ju et al 2022;Zhan et al 2022a). In addition to Yunnan region, Tibet and Xinjiang also developed to be the independent stripe rust epidemiological regions (Li and Zeng 2002;Hu et al 2017;Awais et al 2022).…”
Section: Wheat Rust Epidemiologymentioning
confidence: 99%